Differences in Perceived Severity of Zika Virus Infection and Dengue Fever and its Influence on Mosquito Control Practices in Malaysia - Wong, Li Ping; Alias, Haridah; Aghamohammadi, Nasrin; Sam, I-Ching; AbuBakar, Sazaly (Springer, 2017)
The aims of this study were to explore the differences in (1) the perception of severity towards ZIKV infection and dengue fever, and (2) mosquito control practices before and after the ZIKV outbreak were declared a Public Health Emergency of International Concern (PHEIC). Data were collected between Feb to May 2016 using a computer-assisted telephone interviewing system. The median scale score for perceived severity of ZIKV was 3 (interquartile range [IQR] 1–5) versus 4 (IQR 3–5) for dengue (P < 0.001). The scores for mosquito control practices before and after ZIKV was declared a PHEIC were similar, at 4 (IQR 3–5). Multivariate analysis revealed that participants with a higher score for perception of severity of ZIKV were more likely to report greater mosquito control practices after the declaration of the PHEIC (OR 1.822 [95% CI 1.107–2.998]). The emerging ZIKV pandemic requires concerted efforts to enhance mosquito control practices among the Malaysian public. Efforts to improve public mosquito control practices should focus on enhancing the perception of the severity of ZIKV.